Combinatorial screening of 3D biomaterial properties that promote myofibrogenesis for mesenchymal stromal cell-based heart valve tissue engineering. (August 2017) - Usprech, Jenna; Romero, David A.; Amon, Cristina H.; Simmons, Craig A.
Graphical abstract: Abstract: The physical and chemical properties of a biomaterial integrate with soluble cues in the cell microenvironment to direct cell fate and function. Predictable biomaterial-based control of integrated cell responses has been investigated with two-dimensional (2D) screening platforms, but integrated responses in 3D have largely not been explored systematically. To address this need, we developed a screening platform using polyethylene glycol norbornene (PEG-NB) as a model biomaterial with which the polymer wt% (to control elastic modulus) and adhesion peptide types (RGD, DGEA, YIGSR) and densities could be controlled independently and combinatorially in arrays of 3D hydrogels. We applied this platform and regression modeling to identify combinations of biomaterial and soluble biochemical (TGF-β1) factors that best promoted myofibrogenesis of human mesenchymal stromal cells (hMSCs) in order to inform our understanding of regenerative processes for heart valve tissue engineering. In contrast to 2D culture, our screens revealed that soft hydrogels (low PEG-NB wt%) best promoted spread myofibroblastic cells that expressed high levels of α-smooth muscle actin (α-SMA) and collagen type I. High concentrations of RGD enhanced α-SMA expression in the presence of TGF-β1 and cell spreading regardless of whether TGF-β1 was in the culture medium. Strikingly, combinations of peptides that maximized collagen expression depended on the presence or absence of TGF-β1, indicating that biomaterial properties can modulate MSC response to soluble signals. This combination of a 3D biomaterial array screening platform with statistical modeling is broadly applicable to systematically identify combinations of biomaterial and microenvironmental conditions that optimally guide cell responses. Statement of significance: We present a novel screening platform and methodology to model and identify how combinations of biomaterial and microenvironmental conditions guide cell phenotypes in 3D. Our approach to systematically identify complex relationships between microenvironmental cues and cell responses enables greater predictive power over cell fate in conditions with interacting material design factors. We demonstrate that this approach not only predicts that mesenchymal stromal cell (MSC) myofibrogenesis is promoted by soft, porous 3D biomaterials, but also generated new insights which demonstrate how biomaterial properties can differentially modulate MSC response to soluble signals. An additional benefit of the process includes utilizing both parametric and non parametric analyses which can demonstrate dominant significant trends as well as subtle interactions between biochemical and biomaterial cues.